2013
DOI: 10.1016/j.jinf.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus meningitis: A rare clinical manifestation of central nervous system aspergillosis. Case report and review of 92 cases

Abstract: Aspergillus meningitis may occur in both immunocompetent and immunocompromised patients and run an acute or chronic course. The findings of this systematic review extend the information on this life-threatening infection and could assist physicians in achieving an improved outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
96
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 88 publications
4
96
0
1
Order By: Relevance
“…Zhu et al [5] have reported that there was no decline in immune function in a patient infected with Aspergillus, in spite of the presence of brain-occupying lesions caused by Aspergillus infection. The clinical manifestations of this case resemble those of another 93 cases reported by Antinori et al, [6] of which 55.9% (52 cases) showed no decline in immune function and no predisposing factors. Therefore, fungal infections can also occur in people with normal immune function.…”
Section: Diagnosis Of Central Nervous System Parasitic and Fungal Infsupporting
confidence: 80%
“…Zhu et al [5] have reported that there was no decline in immune function in a patient infected with Aspergillus, in spite of the presence of brain-occupying lesions caused by Aspergillus infection. The clinical manifestations of this case resemble those of another 93 cases reported by Antinori et al, [6] of which 55.9% (52 cases) showed no decline in immune function and no predisposing factors. Therefore, fungal infections can also occur in people with normal immune function.…”
Section: Diagnosis Of Central Nervous System Parasitic and Fungal Infsupporting
confidence: 80%
“…The diagnosis is challenging, as radiological findings are nonspecific and cerebrospinal fluid (CSF) cultures are positive only in less than one-third of cases (3,4). Moreover, obtaining brain tissue for histopathological examination, the diagnostic gold standard, is frequently not feasible.…”
mentioning
confidence: 99%
“…However, its diagnostic performance has been studied very little. To date, only 3 studies including a total of 25 patients have described the value of CSF GM, only 2 of which were carried out with patients with suspected CA (3,6,7). In these 2 studies, CSF GM optical density indexes (ODI) were higher in patients with CA than in those without CA, and sensitivity and specificity were 80% and 100% (6,7).…”
mentioning
confidence: 99%
“…Although other filamentous fungi have been documented as causes of human meningitis and/or encephalitis, most of these infections have been diagnosed postmortem (19, 20). Furthermore, the sensitivity of fungus culture for detection of molds in CSF is very low (13,18). A PCR method for detecting A. fumigatus in CSF has been proposed by Hummel et al; however, its performance has not been well established since only a small number of cases have been evaluated (13,21).…”
mentioning
confidence: 99%
“…Recently, an outbreak of fungal meningitis caused by A. fumigatus was reported in post-tsunami Sri-Lanka and linked to the use of contaminated material during spinal anesthesia (14,15). Among filamentous fungi, A. fumigatus is the most common cause of invasive fungal infections in clinical settings, so most of the available fungal detection methods target this organism and often rely on culture, antigen, and/or radiological findings (16)(17)(18). Although other filamentous fungi have been documented as causes of human meningitis and/or encephalitis, most of these infections have been diagnosed postmortem (19,20).…”
mentioning
confidence: 99%